PENGARUH PERSIAPAN BELAJAR TERHADAP HASIL BELAJAR SISWA SEBAGAI ASESMEN DALAM BIMBINGAN DAN KONSELING - Sandra Sari Saputri; Wahidah Fitriani; Arikah Husnah (INSTITUT AGAMA ISLAM NEGERI METRO, 2023)
The Importance of Guidance and Counseling Assessment in the field of study to optimize student development in the academic field Achieving good learning outcomes requires good learning preparation. The findings in the field were 12 students who had poor learning outcomes and after conducting interviews, it was found that these students were not optimal in preparing for learning. This study aims to describe the learning preparation of UPT SMPN 2 Sitiung students, the learning outcomes of SMPN 2 Sitiung students and to examine the effect of learning preparation on student learning outcomes at UPT SMPN 2 Sitiung. This research is a correlational quantitative descriptive study. The population of this study was students in grades 7, 8, and 9 of UPT SMPN 2 Sitiung who were enrolled in the 2022/2023 academic year with a total of 150 and a sample size of 71 students who were selected using a stratified random sampling technique. Study preparation data was obtained using a questionnaire and learning outcome data obtained from report card scores in July-December for the 2022/2023 school year. The results showed that students' learning preparation was generally good at the level of 65.9% and learning outcomes were in the good category with an average score of 77.1. The results of the simple linear regression test and the significance test obtained from the simple linear regression equation data, the contribution contributed by variable X to variable Y is 49.9% with a value of r = 0.706. The results of the analysis using a significant test T count (20.77) > Ttable (1.996) then Ho is rejected, thus meaning that there is a significant influence between learning preparation on learning outcomes.